O mercado de trabalho para pessoas com deficiência: uma análise comparativa entre Amazonas e Brasil - Neves, Renan Barbosa (Brasil, 2024)
This article aims to make a comparative of the job market for people with disabilities through the economic aspect between Amazonas and Brazil. To the this, the concept of Persons with Disabilities (Pwd) and the job market will be discussed. As a methodology, the deductible method will be adopted with the aim of discussing a specific fact in light of a broader situation. Therefore, the preparation of the literature review will be carried out through bibliography research. The data that will be analyzed was extracted from the Annual Information Report (RAIS) from 2017 to 2021.